A new rotifer species: Lecane langsenensis n. sp. (Rotifera: Monogononta) from Vietnam - Trinh-Dang, Mau; Phan, Doan Dang; Vo, van Minh (Zootaxa, 2019)
Lecane langsenensis n. sp. is described from two locations in Vietnam: Lang Sen Reserve, Long An Province, and the Huong River, Thua Thien Hue Province. It is distinguished from L. arcula, L. aculeata and L. superaculeata by its longer lorica, antero-lateral spine, and claws. Moreover, the size and shape of L. langsenensis, L. arcula, L. aculeata, and L. superaculeata were measured and compared. The results showed that these species are completely different.